Enhancing ICT for insurance in Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study assesses how enhancing information and communication technology (ICT) affects life insurance and non-life insurance in a panel of forty-eight African countries with data for the period 2004-2014. The adopted ICT dynamics are: mobile phone penetration, internet penetration and fixed broadband subscriptions. The empirical evidence is based on Generalized Method of Moments. The results show that enhancing mobile phone penetration and fixed broadband subscriptions has a positive net effect on life insurance consumption while enhancing fixed broadband subscriptions also has a positive net impact of on non-life insurance penetration.
Keywords: I28; I30; L96; O16; O55; 330; Insurance; Information technology